CRITICAL REVIEW ON OPTIMIZING HEALTHCARE SERVICES THROUGH TECHNOLOGICAL INTEGRATION AND INNOVATION - 1Dafer Ahmad Saleh AL Saleh, 2Sari Ahmed Salem Al Sari, 3Saleh JafeeshGhanem Al Jafeesh, 4Fahad Mahdi Alshaibah, 5Yahay AhamadLajam, 6Tarek Saleh AlSaeedah, 7ALI RASHED ALI ALABBAS, 8Mohammed SolemanAlmakrami (Chelonian Research Foundation, 2023)
The combination of innovation and advancement in healthcare has been a parcel of consideration for a long time. This introductory survey assesses the effect of innovation integration on improving in quality of care. Through a comprehensive writing audit, diverse strategies and discoveries were analyzed to explain the role of innovation in making strides toward well-being. Fundamental findings highlight innovation integration's numerous benefits, challenges, and openings. The taking-after talk plunges into the suggestions of these discoveries and offers recommendations for future propels in therapeutic innovation. Critically, this audit highlights the significance of utilizing new innovations to progress healthcare and make strides toward patient outcomes. Keywords: Healthcare services, Technological integration, Innovation, Optimization, Literature review